2021
DOI: 10.1039/d1cb00009h
|View full text |Cite
|
Sign up to set email alerts
|

Bioorthogonal protein labelling enables the study of antigen processing of citrullinated and carbamylated auto-antigens

Abstract: Proteolysis is fundamental to many biological processes. In the immune system, it underpins the activation of the adaptive immune response: degradation of antigenic material into short peptides and presentation thereof...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…Studies in fibroblasts show that exposure to cyanate or urea can drive accumulation of intracellular homocitrullinated peptides and that these modified peptides can then be removed via proteasomal degradation (51). As seen in the context of autoimmune disease, homocitrullination of proteins can alter proteolytic cleavage and lead to MHC presentation of neoepitopes (27,38,52). However, the presence of diverse alleles that can recognize Hcit-specific peptides and the widespread presence of homocitrullinated peptides leads us to believe that this system may have a role in normal cell surveillance (10).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in fibroblasts show that exposure to cyanate or urea can drive accumulation of intracellular homocitrullinated peptides and that these modified peptides can then be removed via proteasomal degradation (51). As seen in the context of autoimmune disease, homocitrullination of proteins can alter proteolytic cleavage and lead to MHC presentation of neoepitopes (27,38,52). However, the presence of diverse alleles that can recognize Hcit-specific peptides and the widespread presence of homocitrullinated peptides leads us to believe that this system may have a role in normal cell surveillance (10).…”
Section: Discussionmentioning
confidence: 99%
“…This cell line was chosen due to its excellent imaging properties and our previous experience in using it as an in vitro model cell line for optimising bioorthogonal chemistry to study dendritic cell biology. [59] The Alexa Fluor-10.1002/anie.202207640…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to cell‐free medium results, 6 – 8 and 19 – 20 exhibited successful ligation after uptake of 1 by DC2.4 dendritic cells [58] . This cell line was chosen due to its excellent imaging properties and our previous experience in using it as an in vitro model cell line for optimising bioorthogonal chemistry to study dendritic cell biology [59] . The Alexa Fluor‐based dyes 9 – 11 were unable to react with 1 in live cells.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently reported the application of "click antigens" as tool to visualize antigen routing and processing in the context of living APCs. [14] These are recombinant antigen proteins containing bioorthogonal handles that are specifically reactive only in so-called 'click' reactions. [15] Click reactions are highly efficient bioorthogonal reactions, that enable selective conjugation of (bio)molecules labelled with a certain reactive group, without influencing the non-labelled molecules present in the cell or lysate.…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that visualization of internalized click antigens could be achieve by CuAAC mediated fluorophore conjugation. [14] Incorporation of bioorthogonal amino acids introduces only minor changes in the protein structure, [14,22] while azide remains stable inside the lysosome for up to 24 hours, allowing for the imaging of antigen processing even when the antigen is degraded. [23] We hypothesized that the click antigen approach might also find application in a chemical proteomics platform.…”
Section: Introductionmentioning
confidence: 99%